1998
DOI: 10.1073/pnas.95.14.8175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes expressed in human CD34+hematopoietic stem/progenitor cells by expressed sequence tags and efficient full-length cDNA cloning

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 42 publications
(27 reference statements)
3
96
0
Order By: Relevance
“…The cDNA was then resequenced in the reverse direction and subsequently deposited on the database (GenBank accession number AF038960). Compared with the full-length DNA sequence of human SKD1 (Mao et al, 1998), hVPS4 lacks the first seven N-terminal amino acids.…”
Section: Dna Manipulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA was then resequenced in the reverse direction and subsequently deposited on the database (GenBank accession number AF038960). Compared with the full-length DNA sequence of human SKD1 (Mao et al, 1998), hVPS4 lacks the first seven N-terminal amino acids.…”
Section: Dna Manipulationsmentioning
confidence: 99%
“…Comparison with a mouse Vps4p-related protein, mSKD1 (Périer et al, 1994), and human SKD1 (designated hSKD1; Mao et al, 1998), indicated that the hVPS4 insert was missing the first seven amino acids of the protein (Figure 1). For our studies we used cDNA constructs containing this truncated hVPS4 or full-length mouse SKD1.…”
Section: Mammalian Vps4mentioning
confidence: 99%
“…[15][16][17][18] Ross et al 15 reported a screening strategy similar to the one we report using cDNA amplified from adaptor-ligated ds cDNA. The method described here has several advantages over the method of Ross et al in that isolation of polyA RNA was not necessary for our cDNA amplifications.…”
Section: Resultsmentioning
confidence: 97%
“…4). Moreover, there are two visible PCR bands in most non-neural tissues, except testis, indicating a possible presence of at least two splice variants of the mSC2 transcript, like the human mSC2 homolog (9). In fact, the extra PCR band observed in various tissues was subjected to DNA sequencing, and the obtained sequence was compared with mSC2 and other mammalian SC2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Vector sequences and ''trash'' sequences, defined as sequences from bacterial sequences and primer polymers, sequences containing >3% of ambiguous bases, and sequences <100 bp long, were removed. The searched results were re-confirmed against the GenBank database for sequence similarity (9).…”
Section: Methodsmentioning
confidence: 99%